2021
DOI: 10.3390/educsci11050192
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Transformational Giftedness

Abstract: This article discusses kinds of transformational giftedness, or giftedness that makes a positive, meaningful, and possibly enduring difference to the world. We extend previous work by suggesting that there are two kinds of transformation that matter: self-transformation and other-transformation. Combining these two kinds of transformation yields a 2 × 2 grid of four kinds of giftedness: non-transformational giftedness (no transformation), transformational giftedness (self- and other-transformation combined), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 30 publications
0
40
0
1
Order By: Relevance
“…In some recent writing (e.g., Sternberg, 2020aSternberg, , 2020bSternberg, , 2021Sternberg et al, 2021) extending previous literature on kinds of leadership (Bass & Riggio, 2006), it has been suggested that society view giftedness as comprising at least two complementary kinds-transactional and transformational. The kinds differ not in level of gifts, but rather in deployment of gifts-how individuals choose to utilize their giftedness.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…In some recent writing (e.g., Sternberg, 2020aSternberg, , 2020bSternberg, , 2021Sternberg et al, 2021) extending previous literature on kinds of leadership (Bass & Riggio, 2006), it has been suggested that society view giftedness as comprising at least two complementary kinds-transactional and transformational. The kinds differ not in level of gifts, but rather in deployment of gifts-how individuals choose to utilize their giftedness.…”
mentioning
confidence: 88%
“…Can such transformationally gifted individuals be identified as young people? A recently published fully open-access scale can be used to measure transformational giftedness (see Sternberg et al, 2021). It is not designed to replace traditionally transactionally-oriented measures.…”
mentioning
confidence: 99%
“…An interesting parallel is in the recent writing of Sternberg [6,28]. He separates gifted people into the same two types, presenting evidence that methods for defining giftedness and identifying gifted people now and in the in the past have resulted in selecting those who are transactionally gifted.…”
Section: Transformational Giftedness: An Important Type Of Giftedness For the 21st Centurymentioning
confidence: 99%
“…We need to identify and cultivate giftedness that is transformative, "that by its very nature seeks positively to change the world at some level-to make the world a better place" [6] p. 231. He further expands the concept to include both self-and other-transformation [28]. This is not a new concept.…”
Section: Transformational Giftedness: An Important Type Of Giftedness For the 21st Centurymentioning
confidence: 99%
“…Or anywhere, really? I believe a clue can be found in a recently proposed concept of transformational giftedness [24][25][26]. The basic idea of the concept, building on the concepts of transformational and transactional leadership, is that giftedness can be divided into two main kinds-transactional and transformational [27][28][29].…”
mentioning
confidence: 99%